An improved averaged value model of MMC-HVDC for power system faults simulation. (September 2019) - Song, Guobing; Wang, Ting; Huang, Xinghua; Zhang, Chenhao
Highlights: An improved average value model (AVM) of modular multilevel converter (MMC) for large-scale system simulation. Accurate performance in all types of faults and blocked state of MMC. Easy modelling in commonly used software packages. Abstract: Detailed model (DM) of modular multilevel converter (MMC) brings about a high computational burden for electromagnetic transient (EMT) simulation. Therefore averaged value model (AVM) of MMC is proposed for fast simulation of large-scale multi-terminal HVDC system. No direct electrical contact exists between AC and DC system in conventional AVM and therefore the coupling relationship among electric quantities in fault analysis could not be accurately modelled. In order to solve the aforementioned problem, an improved AVM (IAVM) of half-bridge (SB) MMC topology is proposed. All capacitor voltages of AVM are constant and an arm is directly equivalent to a controlled voltage source. The proposed AVM can be applied for the DC faults and blocking conditions by introducing a group of switches connecting AC and DC sides. Two extra controlled voltage sources are introduced for correct DC voltage offset in AC voltages under DC line-to-ground (LTG) faults. Simulation results verify the accuracy and efficiency of the IAVM. IAVM could be implemented in commonly used software packages and is suitable for power system fault analysis.